PENGARUH KEPEMILIKAN INSTITUSIONAL, LEVERAGE, DAN FINANCIAL DISTRESS TERHADAP KONSERVATISME AKUNTANSI - Windi Lestari; Suwandi Suwandi (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2023)
This research aims to analyze the influence of institutional ownership, leverage, and financial distress retirement to the accounting conservatism. The population of the research is the manufacturing companies in the basic industry and chemical sectors listed on IDX in the period of 2019 until 2021. The research sample consisted of 72 samples selected based on purposive sampling technique. This study uses quantitative methods with secondary data sources in the form of complete company annual reports. Data analysis technique in this study used linear regression analysis. The results showes that the variable leverage and financial distress has a significant effect on accounting conservatism. Meanwhile variables institutional ownership do not have a significant effect  on accounting conservatism